Expected Losses, Unexpected Costs? Evidence from SME Credit Access under IFRS 9 - Ertan, Aytekin (The Accounting Review, 2025)
ABSTRACT This paper examines lending effects of European banks switching to an expected credit loss (ECL) model under IFRS 9. I find evidence that ECL transition deteriorates the credit landscape for SMEs—as risky, opaque, and bank-dependent borrowers. Post-ECL, affected banks reduced SME lending by over 10 percent, and these effects persisted during the most recent downturn during the COVID-19 pandemic. Banks’ financial reporting objectives and implementation difficulties seem to explain these findings. Additional tests at the borrower and loan-contract levels indicate rising loan rejection rates, interest spreads, and collateral requirements, as well as declining loan amounts, maturities, and subsequent capital investments, for SMEs that do business with affected banks. JEL Classifications: G21; G28; G38; M41.